2003
DOI: 10.1007/978-3-540-45080-1_27
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Several Cluster Number Selection Criteria

Abstract: Abstract. The selection of the number of clusters is an important and challenging issue in cluster analysis. In this paper we perform an experimental comparison of several criteria for determining the number of clusters based on Gaussian mixture model. The criteria that we consider include Akaike's information criterion (AIC), the consistent Akaike's information criterion (CAIC), the minimum description length (MDL) criterion which formally coincides with the Bayesian inference criterion (BIC), and two model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Hu and Xu [91] presented a comparative study of the probabilistic criteria, including Akaike's information criterion (AIC) [92], consistent Akaike's information criterion (CAIC) [93], minimum description length (MDL) [94], Bayesian Ying-Yang (BYY) harmony empirical learning criterion (BYY-HEC) [72] and BYY harmony data smoothing learning criterion (BYY-HDS) [95] using Gaussian mixture based clustering. The results indicated that BYY-HDS was superior to the other criteria.…”
Section: Traditional Approachesmentioning
confidence: 99%
“…Hu and Xu [91] presented a comparative study of the probabilistic criteria, including Akaike's information criterion (AIC) [92], consistent Akaike's information criterion (CAIC) [93], minimum description length (MDL) [94], Bayesian Ying-Yang (BYY) harmony empirical learning criterion (BYY-HEC) [72] and BYY harmony data smoothing learning criterion (BYY-HDS) [95] using Gaussian mixture based clustering. The results indicated that BYY-HDS was superior to the other criteria.…”
Section: Traditional Approachesmentioning
confidence: 99%
“…Guo [21] proposed a cluster number choice method for a small set of samples using a Bayesian Ying-Yang (BYY) model. Comparative studies such as [17] and [22] provided experimental comparisons of many criteria such as Akaike's Information Criterion (AIC), Minimum Description Length (MDL), and (BYY) for determining the number of clusters based on a Gaussian mixture model. A variety of statistical techniques for tendency assessment are discussed in the work of Jain and Dubes [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our visualization analysis on five datasets reveals that there are extremely complex cluster structures, i.e., the datasets contain a large number of classes, unbalanced cluster membership, low intracluster dissimilarity, high intercluster similarity, high dimensionality, and arbitrary cluster shapes, which results in failures for existing clustering algorithms including ours. Moreover, our empirical studies along with others [21], [32], [33], [37]- [40] indicate that our RPCL network ensemble on four representations described in Section II performs well for only the data with balanced and a small number of clusters structures, which is caused by the limitation of the coarse representations and RPCL network.…”
Section: A Experiments On Clustering Analysismentioning
confidence: 99%